Developing indicators to assess the viability of small- and medium-scale farms: a case study of market gardening farms at the regional scale - Heine, Benjamin; Gaspart, Frédéric; Biot, Nicolas (Frontiers in Sustainable Food Systems, 2025)
Small-and medium-scale market gardening plays an important role in transitioning toward a sustainable food system, yet its viability remains underexplored. This study assesses the viability of small- and medium-scale market gardening farms in the Coeur de Condroz region (Belgium) using field data from 17 farms. A set of five indicators; land productivity, labor productivity, gross added value, estimated profit, and a risk index were developed to analyze viability. Results reveal significant variability among farms. Some achieve viability, while others rely on off-farm income. Three distinct farm profiles were identified based on viability indicators; one composed of less performant farms and two of viable farms with different strategies. Key drivers of viability were highlighted to include greenhouse surface, crop diversity, and years since establishment. Additionally, farms integrating complementary on-farm activities exhibited lower risk of cost but lower productivity per hectare. By redefining viability assessment methods and engaging directly with farmers, this research offers valuable insights into the factors shaping small-and medium-scale market gardening farms. Findings indicate that viability cannot be measured through financial indicators alone but must consider broader socio-economic dimensions. Additionally, farmers' perceptions of viability vary, with some incorporating quality of life into their assessment. This study demonstrates that market gardening can be viable through diverse strategies, despite limited public financial support. It offers practical recommendations for research, and also highlights the potential of applying this methodology to cross-regional longitudinal studies, as well as the need to investigate the relationship between perceived and measured viability.